Analitični model določevanja mehanskih lastnosti biopolimernih kompozitov - mikromehanski postopek - Hančič, Aleš (Strojniški vestnik, 2007)
The development of a new composite that is made up of natural fibres and low-price polymers, such as HDPE or PP, began in the 1990s. Because this material is relatively new to the market and due to the random characteristics of the fibres, no attempts have been made to analytically define the mechanical properties of this material. In this paper a micro-mechanical approach, called the generalised method of cells (GMCs), is introduced to describe the properties of injection-moulded wood-plastic composites made up of polypropylene (PP) or polystyrene (PS) and wood or cellulose short fibres. The main problem with an analytical approach is that the natural fibres are not uniform in shape and size, which makes them hard tofit into standard mathematical models. In this paper the average values of the fibre sizes were used. The materials were first scanned with optical and electron microscopes to determine the fibre properties and their scatter. These values were then used to determine the elastic and plastic response of the composite together with the maximum strength and elongation of the composite, where the Tsai-Hill failure-criterion was used. The results were then compared to the experimental data in order to evaluate the practical usefulness of this method. The time-dependent mechanical behaviour of the composite was not considered due to the complex and random properties of the fibre.
Keywords: biopolimeri; kompoziti; naravna vlakna; mehanske lastnosti